Synthesis and Antioxidant and Antibacterial Activities of Metal-Based Schiff Bases of Nicotinoyl, Isonicotinoyl and Benzoyl Hydrazides - Hussain, M.; Shafiq, Z.; Hussain, A.; Yaqub, M.; Arshad, S.; Ashraf, M.; Abbasi, B.H.; Ahmad, H.B. (Asian Journal of Chemistry, 2012)
A series of 15 metal based [Cu(II), Co(II) and Ni(II)] complexes have been synthesized with novel N'-[-(5-hydroxy-2-nitrophenyl)-methylidene]pyridine-4-carbohydrazide (L1), N'-[-1-(2,5-dihydroxyphenyl)ethylidene]pyridine-3-carbohydrazide (L2), N'-[-1-(5-chloro-2- hydroxphenyl)ethylidene]pyridine-3-carbohydrazide (L3), N'-[-1-(5-chloro-2-hydroxyphenyl)ethylidene]pyridine-4-carbohydrazide (L4) and N'-[-1-(2,5-dihydroxyphenyl)ethylidene]-3-hydroxybenzohydrazide (L5) Schiff bases and screened for antioxidant and cytotoxic activities. All these complexes exhibited strong antioxidant activity against DPPH radical. Antibacterial activity assay exhibited MIC50 values of these compounds comparable to standard drugs for both Gram-positive and Gram-negative bacteria.